Macromodeling approach for pushover analysis of textile-reinforced mortar-strengthened masonry - Oliveira, Daniel V. (2019)
The strengthening of masonry structures using composite-based solutions has received significant research attention in recent years due to their proved considerable influence on enhancing structural characteristics, for example, stiffness and strength. In spite of the all achieved advances, numerous drawbacks have been noticed, in particular when conventional fiber-reinforced polymers are used. Thus novel techniques such as textile-reinforced mortar (TRM) have been introduced to overcome these issues. This chapter addresses key aspects of nonlinear finite element modeling of TRM composites. It mainly discusses the macromodeling approach as it requires fewer details (material characteristics) and less computational effort with respect to the micromodeling strategy, making it possible to use this approach in complex practical projects. Experimentally observed behaviors and characterization of required material properties are considered and knowledge gaps are highlighted. Finally, a series of numerical macromodeling applications on masonry structures are discussed, involving different construction materials. Pushover analyses are conducted to assess the influence of TRMs on both in-plane and out-of-plane seismic responses